EFEKTIFITAS PEMBELAJARAN CTL (CONTEXTUAL TEACHING AND LEARNING) MATA PELAJARAN IPS DALAM MENINGKATKAN MOTIVASI BELAJAR DAN PERILAKU PROSOSIAL SISWA KELAS IX SMPN 2 PONJONG GUNUNG KIDUL - Tukiman, Tukiman (Jurnal Psikologi Terapan dan Pendidikan, 2013)
ABSTRACTThis study was conducted based on the observation of class IX student that showed low motivation and prosocial behavior. The research objective is to examine how contextual teaching and learning in social studies improves learning motivation and student’s prosocial behavior. The sample of study was 30 students taken from class IX student SMP 2 Ponjong Gunung Kidul. A scale was used to obtain the data of motivation and student’s prosocial behavior. Based on the analysis it can be concluded that the learning method CTL (contextual teaching and learning) is effective in increasing motivation to learn. The post-test mean score greater than the mean pre- test score (141.23> 121.80), with the t test -18.525 Besides, CTL method increased prosocial behavior.Keywords: CTL, motivation to learn, and prosocial behavior